Funcionarios Escuela de Educación. (UNED, 2025)
Cecilia Balmaceda, Eugenia Brenes, Ligia Picado, Maricruz Corrales, Leda Vásquez, Elizabeth Shing, Flor Chacón , Julio Aguilar, Hellen Valverde, Beltrán Lara, Fernando Brenes, Maritza Meza